2011
DOI: 10.1021/om200576f
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) Hydrido Complexes Having a Primary Silyl or Germyl Ligand: Synthesis, Crystal Structures, and Dynamic Behavior

Abstract: The first examples of palladium(II) hydrido complexes having a dihydrosilyl or dihydrogermyl ligand, [PdH(EH2Trip)(dcpe)] (E = Si (2), Ge (4); dcpe = 1,2-bis(dicyclohexylphosphino)ethane), were synthesized by oxidative addition of an overcrowded primary silane and germane, TripEH3 (E = Si (1), Ge (3); Trip = 9-triptycyl) with [(μ-dcpe)Pd]2 in toluene. The molecular structures of complexes 2 and 4 were established by single-crystal X-ray analysis, which showed a distorted-square-planar geometry around the palla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
(26 reference statements)
0
32
0
Order By: Relevance
“…Related reversible processes involving the addition of silanes and germanes to [Pd 2 (dcpe) 2 ] (dcpe ¼ 1,2-bis(dicyclohexylphosphino)ethane) have been reported to form [Pd(dcpe)(H)(ER 3 )] (E ¼ Si, Ge). 36,37 In these instances, s-silane or s-germane complexes are invoked only as unstable intermediates in reversible redox processes that involve the oxidative addition and reductive elimination of the E-H bond to the palladium centre. Despite the precedent for 4, at this time we cannot unambiguously rule out its assignment as a linear two coordinate complex formed from phosphine dissociation from Pd.…”
Section: Reactions Of Alanes With Palladium Complexesmentioning
confidence: 99%
“…Related reversible processes involving the addition of silanes and germanes to [Pd 2 (dcpe) 2 ] (dcpe ¼ 1,2-bis(dicyclohexylphosphino)ethane) have been reported to form [Pd(dcpe)(H)(ER 3 )] (E ¼ Si, Ge). 36,37 In these instances, s-silane or s-germane complexes are invoked only as unstable intermediates in reversible redox processes that involve the oxidative addition and reductive elimination of the E-H bond to the palladium centre. Despite the precedent for 4, at this time we cannot unambiguously rule out its assignment as a linear two coordinate complex formed from phosphine dissociation from Pd.…”
Section: Reactions Of Alanes With Palladium Complexesmentioning
confidence: 99%
“…The former signal was assigned to the PMe 3 trans to the hydrido ligand using a non 1 H-decoupled 31 P NMR technique at 253 K. The 29 Si{ 1 H} NMR spectrum of 5 at 223 K featured one 29 Si resonance as a broad doublet signal at δ = −43.9 ( 2 J Si-P = 151 Hz). The broadening of NMR signals possibly implies the existence of the Si-H σ-complex intermediate 6 in the NMR time scale [38,41,42]. Unfortunately, attempts to probe further the fluxional behavior of 5 by VT (variable temperature)-NMR in solution revealed no appreciable changes in spectroscopic features by 1 H and 31 P NMR spectroscopy.…”
Section: Ligand Exchange Reactions Of 2 With Free Phosphine Ligandsmentioning
confidence: 99%
“…Meanwhile, we succeeded in the first isolation of a series of hydrido(dihydrogermyl) platinum(II) complexes [PtH(GeH 2 Trip)(L)] (Trip = 9-triptycyl) using a bulky substituent, 9-triptycyl group [37]. In addition, we reported the first syntheses and structural characterizations of hydrido palladium(II) complexes with a dihydrosilylor dihydrogermyl ligand, [PdH(EH 2 Trip)(dcpe)] (E = Si, Ge) [38]. Very recently, we also found that hydride-abstraction reactions of [MH(EH 2 Trip)(dcpe)] (M = Pt, Pd, E = Si, Ge) with B(C 6 F 5 ) 3 led to the formations of new cationic dinuclear complexes with bridging hydrogermylene and hydrido ligands, [{M(dcpe)} 2 (µ-GeHTrip)(µ-H)] + [39].…”
Section: Introductionmentioning
confidence: 99%
“…Closely related to germylene and germylyne complexes are transition‐metal germyl complexes, which have been known for a long time and have continuously received considerable attention over the last several decades, mainly because of their relevance to the catalytic transformations involving germanium, and materials chemistry. [12a], The most versatile methods for the synthesis of transition‐metal germyl complexes involve either oxidative addition of the Ge–X bond GeXR 3 (X = H, Cl)[12a], or insertion of dihalogen species GeX 2 into the M–X bond[12a], [13a], , to give triorgano M‐GeR 3 or trihalogen M‐GeX 3 germyl derivatives. However, despite of the large number of germyl complexes of transition metals that have been prepared in recent years, ruthenium germyl complexes are still much less common,[13a], [15c], , , while the osmium congeners are even more limited , , , …”
Section: Introductionmentioning
confidence: 99%